Investigation on the Sequestration of Divalent Metal Ions Employing Animal Waste - Andal, N. Muthulakshmi; Gayathri, N. S.; Anuradha, J. (Challenges and Advances in Chemical Science Vol. 3, 2021)
Heavy metal ions are toxic to the eco-system, when the exceed their concentrations as per specific standards. The widespread use of these in industries control havoc, therefore considerable attention in given for their reduction and removal. It is necessary to develop novel materials in environment order to chelate these toxicants in environmental samples. Based on this need for developing zero cost sorbent, the present study aims at investigating the sorption capacity of Goat Hooves, a no cost material, in the process of removal of Pb(II) and Cd(II) ions from aqueous media. Goat hooves are subjected Fourier Transform Infra-Red spectroscopy / Scanning Electron Microscopy analyses, post proper treatment (TGH), to identify the functional groups and describe its surface morphology respectively. Batch equilibration experiments are conducted to verify the impact of varied operating parameters viz., particle size, dosage, initial concentration, contact time and pH. The obtained data are modelled using Langmuir, Freundlich and Temkin isotherms. Langmuir plot exhibited better linearity amongst other derived models indicating of monolayer adsorption to be followed by Pb(II) – TGH and Cd(II)- TGH. Further, Statistical tool analyses using SPSS 20 software, recorded a significant correlation value when applied to the optimized conditions of the batch studies.